Enhancing Eco-Print Product Quality Through Women’S Creative Empowerment: A Community-Based Approach In Gunungpati, Semarang - Roudlotus Sholikhah; Widowati Widowati; Sri Endah Wahyuningsih (Jurnal Abdi Masyarakat Indonesia, 2026)
Female artisans who are members of the Family Welfare Program (PKK) in Gunungpati, Semarang City, face issues with unstable eco-print quality, particularly in areas of colorfastness, pattern clarity, and neatness of finishing, which makes their products less competitive. The goal of this community service activity is to enhance the quality of eco-print products while empowering women's creativity through training and mentoring using a participatory approach. This activity was conducted for 25 PKK participants through training in basic and advanced eco-printing techniques, hands-on practice, production assistance, and evaluation of the activity results. Evaluation was conducted using a product quality rubric and a simple questionnaire before and after the program. The results of the activity showed an increase in product quality, characterized by more stable colors, clearer patterns, and neater finishing. In addition, the participants experienced increased skills, confidence in their work, and the ability to work in groups. This activity also stimulated the idea of ​​​​marketing eco-print products as a source of additional income. This program has proven that participatory training and mentoring are effective ways to improve the quality of environmentally friendly products and strengthen the creative economic capacity of women at the community level.